COMPARATIVE ANALYSIS OF MEDICAL STUDENTS’ PERCEPTIONS OF ATTITUDES, ETHICS AND COMMUNICATION (AETCOM) TRAINING: ROLE-PLAY VERSUS SIMULATED PATIENTS - V., POONGAVI; M. R., MANASA; K., SWETHA; KANNAN, ATHULYA (International Journal of Pharmacy and Pharmaceutical Sciences, 2025)
Objective: To evaluate medical students’ perceptions of learning AETCOM through role plays and simulated patients, as well as their attitudes towards communication skills learning. Methods: We conducted this prospective study after obtaining ethical approval. The second year MBBS students’ attitude towards communication skills learning was assessed using rees and Sheard’spre validated 26 item questionnaire on Communication Skills Attitude Scale (CSAS). It includes 13 positive and 13 negative statements, which were scored using 5 point Likert scale. The students were taught AETCOM module using two teaching methods – role plays and simulated patients. Then their perception towards learning communication by these methods was assessed. Results: There were 143 study participants-74 males and 69 females. The mean age of the participants was 19.2 y. For positive attitude, the mean score was 55.7±8.7, while for negative attitude was 33 ±12.4. mean perception scores were significantly higher for teaching communication skills using simulated patients (48.8±5.3) compared to role plays (46.5±5.2) {p<0.05}. Conclusion: Higher scores for positive attitude and lower scores for negative attitude imply that medical students possess stronger positive attitude for learning AETCOM (communication skills). The medical students preferred learning communication skills using simulated patients rather than role plays.